2020
DOI: 10.1002/ijfe.2107
|View full text |Cite
|
Sign up to set email alerts
|

Financial innovation and economic growth: Empirical evidence from China, India and Pakistan

Abstract: This study investigates the causal relationship between financial innovation and economic growth in China, India, and Pakistan over the period of 1970-2016. Using an Autoregressive Distributed Lag (ARDL) bound testing and Granger causality-based Error Correction Model (ECM), this study finds that financial innovation generally has a positive and statistically significant impact on economic growth in the short-run and long-run. These results show that in the long-run, monetary management and credit flow to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Thus, they found that financial development caused economic growth in Mauritius, Namibia and South Africa. In their study, Nazir et al (2020) support a positive causality from financial development to economic growth. They show that financial innovations in forms of monetary management and credit flow to the private sector are important channels in the financial system for economic growth.…”
Section: Literature Review 21 Finance-growth Nexusmentioning
confidence: 76%
See 2 more Smart Citations
“…Thus, they found that financial development caused economic growth in Mauritius, Namibia and South Africa. In their study, Nazir et al (2020) support a positive causality from financial development to economic growth. They show that financial innovations in forms of monetary management and credit flow to the private sector are important channels in the financial system for economic growth.…”
Section: Literature Review 21 Finance-growth Nexusmentioning
confidence: 76%
“…Firstly, evidence for a positive causality supports the idea that financial development either leads or follows economic growth towards the same or positive direction (Nazir et al, 2020;Shahbaz et al, 2018). Hence, the dominance of a market-based system presupposes the presence of a liberalised economy and a financial system that is open, liberal and market based.…”
Section: Literature Review 21 Finance-growth Nexusmentioning
confidence: 82%
See 1 more Smart Citation
“…However, in order to be consistent with the prevailing literature, this study considers three proxy measures that are widely used in various empirical studies. The first proxy is the broad-to-narrow money (M2/M1), which affects the demand for real cash balances, the income, and interest elasticity for money demand (Arrau and De Gregorio, 1993 ; Ansong et al, 2011 ; Bara and Mudxingiri, 2016 ; Bara et al, 2016 ; Qamruzzaman and Jianguo, 2017 , 2018a , c ; Nazir et al, 2018 ; Qamruzzaman and Wei, 2018 ). For the second measure of financial innovations (FI), this study employs the ratio of M3/M1, following Dunne and Kasekende ( 2018 ), Mannah-Blankson and Belnye ( 2004 ), Ajide ( 2015 ), and Kasekende and Nikolaidou ( 2014 ).…”
Section: Data and Methodology Of This Studymentioning
confidence: 99%
“…Financial innovation, like other types of innovation, is a constant act of integrating changes in the financial sector by improving and diversifying financial goods and procedures (Ang and Kumar 2014). The introduction of new financial resources and infrastructure into the financial system boosts financial services performance and capital market developments, ultimately enhancing growth in the economy (Nazir et al 2021).…”
Section: Introductionmentioning
confidence: 99%